2000
DOI: 10.1038/80868
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-7 mediates the homeostasis of naïve and memory CD8 T cells in vivo

Abstract: The naïve and memory T lymphocyte pools are maintained through poorly understood homeostatic mechanisms that may include signaling via cytokine receptors. We show that interleukin-7 (IL-7) plays multiple roles in regulating homeostasis of CD8+ T cells. We found that IL-7 was required for homeostatic expansion of naïve CD8+ and CD4+ T cells in lymphopenic hosts and for CD8+ T cell survival in normal hosts. In contrast, IL-7 was not necessary for growth of CD8+ T cells in response to a virus infection but was cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

53
1,384
8
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,453 publications
(1,450 citation statements)
references
References 59 publications
53
1,384
8
5
Order By: Relevance
“…1). A number of different cytokines, particularly IL-7 and IL-15, have been reported to be required for survival and maintenance of memory T cells in vivo [26,27,29,30]. In our model system, IL-2 is the only exogenously added cytokine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). A number of different cytokines, particularly IL-7 and IL-15, have been reported to be required for survival and maintenance of memory T cells in vivo [26,27,29,30]. In our model system, IL-2 is the only exogenously added cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…It has become evident that IL-15 controls both homeostatic proliferation and survival of CD8 memory cells in vivo [26,27], possibly by mimicking a TCR response [28]. In addition, IL-7 was also shown to promote homeostatic proliferation in CD8 T cells [29]. Recently, it has been shown that IL-7, but not IL-15, is required for the maintenance of CD4 memory T cells [27,30].…”
Section: Introductionmentioning
confidence: 99%
“…Studies that examine mice deficient in IL-7 or IL-15 have demonstrated that these cytokines have a supportive role in the survival and/or proliferation of adoptively transferred T cells in lymphodepleted hosts [36][37][38][39][40]. The absence of IL-7 inhibits naïve CD4 + and CD8 + T-cell homeostatic proliferation and survival in a lymphopenic environment.…”
Section: Evidence For the Presence Of Homeostatic Cellular Cytokine 'mentioning
confidence: 99%
“…8 IL-7 binds to the dimerized receptors of IL-7 receptor-a (IL-7Ra) (CD127) and the g-chain receptor (CD132) to exert its effect. The IL-7Ra is also found in soluble (s) form, as sIL-7Ra in plasma, and is produced as a result of splicing exon-6 from the IL-7Ra gene mRNA.…”
Section: Introductionmentioning
confidence: 99%